Reclaiming the House of the Representatives from Republicans: Case Study of Districts TX-32 and NJ-3 - Tomaszewski, Norbert (Political Preferences, 2019)
2018 midterm elections in the United States allowed more ethnically and racially diverse candidates to become members of the Congress. The use of social media tools helped them to reach out to their community and get out the vote, which is especially important in Democratic campaign tactics. The article, by focusing on Colin Allred's and Andy Kim's Congressional bids, focuses on how their issue-oriented campaigns helped to mobilize the liberal voters. Furthermore, by analysing the rapidly changing demographics, it tackles the crucial question: do they mean the doom of the Republican Party?